TELEMONITORING AND/OR SELF-MONITORING OF BLOOD PRESSURE IN HYPERTENSION (TASMINH4): A RANDOMISED CONTROLLED TRIAL. (June 2018) - McManus, R.; Mant, J.; Franssen, M.; Nickless, A.; Schwartz, C.; Hodgkinson, J.; Bradburn, P.; Farmer, A.; Grant, S.; Greenfield, S.; Heneghan, C.; Jowett, S.; et al.
Abstract : Objective: Previous studies evaluating titration of antihypertensive medication using self-monitoring have contradictory findings and the precise place of telemonitoring over self-monitoring alone is unclear. The TASMINH4 trial aimed to assess the efficacy of self-monitored blood pressure, with or without telemonitoring, for antihypertensive titration in primary care, compared to usual care. Design and method: Randomised controlled trial in 142 UK General Practices including hypertensive patients, aged over 35, with blood pressure >140/90mmHg who were willing to self-monitor their blood pressure. Randomisation (1:1:1 basis) to medication titration using self-monitored blood pressure, self-monitored blood pressure with telemonitoring or usual care (clinic blood pressure). Neither participants nor investigators were masked to group assignment. The primary end point was difference in systolic blood pressure between intervention and control taking into account baseline covariates and primary analysis was for complete cases without imputation. Trial registration: ISRCTN 83571366 Results: 1182 participants were randomised to antihypertensive titration using self-monitoring (395), telemonitoring (393) or clinic blood pressure (394) of whom 1003 (85%) were included in the primary analysis. After 12 months, systolic blood pressure was significantly lower in both self-monitoring groups (self-monitoring 137.0mmHg, telemonitoring 136.0mmHg) compared to usual care (140.4mmHg): adjusted mean differences vs usual care: telemonitoring -4.7mmHg (95% confidence interval -7.0, -2.4) and self-monitoring alone -3.5mmHg (-5.8, -1.2) with no significant difference between self-monitoring groups (-1.2mmHg (-3.5, 1.2)) [see Table]. Results were similar in sensitivity analyses including multiple imputation and were consistent in pre-specified sub-groups for age, gender, blood pressure target, deprivation and history of cardiovascular disease. Figure. No caption available. Conclusions: Self-monitoring, with or without telemonitoring, when used by General Practitioners to titrate antihypertensive medication in individuals with poorly controlled blood pressure, leads to significantly lower blood pressure than titration guided by clinic readings. With most GPs and many patients using self-monitoring, it could become the cornerstone of hypertension management in primary care.